ANALISIS EROSI DAN SEDIMEN TRANSPOR PADA SUNGAI WANGGU - KENDARI - Sukri, Ahmad Syarif; Prayitno, Noto (Universitas Halu Oleo, 2013)
ABSTRACTWanggu river is one of the rivers which have a very important role for the surrounding community as the people's livelihood for sand mining, which is also important as a source of raw water for drinking water plentiful company of Kendari city.The aims of this study? is to examine the magnitude of actual and potential erosion occurring on the wanggu river every year, and analyzes of the sediment in the wanggu river transport? occurring at the point of observation at the site of sand mining in Baruga districts. The method used to calculate the sediment drift measurement methods for a moment while the method of calculating the basic sediment meyer-peter.The results of the analysis, obtained by erosion of the actual (Ea) 75287.327 tons / ha / year, erosion potential (Ep) of 3,095,568.730 tons / ha / year. As for the average results of laboratory tests for sediment drift on the wangguriver? of 41.93 mg / liter in wanggu river flow in the place of sand mining 9.214 m3/second, basic sediment (Qb) of 41817.00 tons / ha / year and for total sediment 59851.36 tons / ha / year.?Keywords: Erosion, Sediment and River